2018
DOI: 10.1128/mcb.00007-18
|View full text |Cite
|
Sign up to set email alerts
|

RBM4 Modulates Radial Migration via Alternative Splicing of Dab1 during Cortex Development

Abstract: The RNA-binding motif 4 (RBM4) protein participates in cell differentiation via its role in regulating the expression of tissue-specific or developmentally regulated mRNA splice isoforms. RBM4 is expressed in embryonic brain during development; it is initially enriched in the ventricular zone/subventricular zone and subsequently distributed throughout the cerebral cortex. knockout brain exhibited delayed migration of late-born neurons. Using electroporation, we confirmed that knockdown of RBM4 impaired cortica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…While Ptbp1 promotes exclusion of exons 7/8 early during neocortical development, Rbm4 governs their inclusion during mid developmental stages, generating a full-length Dab1 isoform that predominates during migration of later-born neurons. This splicing switch enables phosphorylation of the tyrosine residues of exons 7/8 in response to Reelin signaling, which subsequently activates cytoskeletal machinery and coordinates directional migration (Dhananjaya et al, 2018).…”
Section: Establishment Of the Unique Layered Structure Of The Neocortexmentioning
confidence: 99%
“…While Ptbp1 promotes exclusion of exons 7/8 early during neocortical development, Rbm4 governs their inclusion during mid developmental stages, generating a full-length Dab1 isoform that predominates during migration of later-born neurons. This splicing switch enables phosphorylation of the tyrosine residues of exons 7/8 in response to Reelin signaling, which subsequently activates cytoskeletal machinery and coordinates directional migration (Dhananjaya et al, 2018).…”
Section: Establishment Of the Unique Layered Structure Of The Neocortexmentioning
confidence: 99%
“…The RNA binding protein RBM4 modulates precursor mRNA splicing and mRNA translation. Depletion of RBM4 impairs the differentiation of various cell types, including neuronal cells 1 6 . RBM4 promotes neuronal differentiation by modulating alternative splicing of the cell-fate determinant Numb and the glycolytic enzyme pyruvate kinase M 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%
“…RBM4 promotes neuronal differentiation by modulating alternative splicing of the cell-fate determinant Numb and the glycolytic enzyme pyruvate kinase M 4 , 5 . Moreover, an in-utero experiment demonstrated that RBM4 participates in radial migration of newborn neurons in the developing cerebral cortex by promoting the expression of full-length Dab1 6 , a regulator of Reelin signaling that controls neuronal positioning. However, whether RBM4 is essential for brain development has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative splicing (AS) is one of the major molecular processes underlying increased transcriptome and proteome diversity and associated organismal complexity in metazoans [1][2][3][4] .…”
Section: Introductionmentioning
confidence: 99%